FENOMENA BERBURU TAKJIL DALAM MENINGKATKAN TOLERANSI DI INDONESIA SEBAGAI IMPLEMENTASI NILAI PANCASILA - Febriyanti, Olivia Dwi; Hasasah, Nadiatul; Rahmadhanti, Karina Oktavia; Puspita, Ari Metalin Ika (Universitas Nias Raya, 2024)
Indonesia is a country that has many tribes, races, and religions. However, the existence of many of these differences makes Indonesia a country rich in diversity. The phenomenon that has emerged recently is the